Rancang Bangun Sistem Informasi Dashboard sebagai Pendukung Pengambilan Keputusan Terkait Kinerja Karyawan PT. X - Michelle Steffanny Subagyo (Jurnal Titra, 2022)
This research is conducted to design an HRD Department dashboard at PT. X. PT. X considers employee performance as a crucial aspect as its vision is to always maintain the quality of its service. However, employee performance evaluation is still carried out by manually processing data from separate sources. This condition deters the top level management from making decisions regarding employee performance. This problem can be answered by designing a dashboard to visualize employee performance data. The purpose of this dashboard is to make decision making related to employee performance evaluation easier for top level management. The dashboard is designed using a software where the data are connected and processed. The processed data are visualized using various types of visuals of the dashboard. Overall, the HRD Department dashboard can answer the needs of employee performance evaluations, such as data on employees who receive annual bonuses, the effectiveness of the workshops, as well as employee and department performance score.